The role of international student interactions in English as a lingua franca in L2 acquisition, L2 motivational development and intercultural learning during study abroad - Hessel, Gianna (Studies in Second Language Learning and Teaching, 2019)
Crossing borders features prominently as a theme in study abroad, not only in terms of students’ physical border crossings but also in their intercultural interactions with second language (L2) speakers whose background (linguistic and otherwise) they may perceive as markedly different from their own. Researchers have had a long-standing interest in study abroad participants’ interactions with other L2 speakers abroad for their perceived potential to enhance L2 development, L2 motivation and intercultural learning processes. The focus of existing studies in this area has been on the interactions of study abroad participants with host national students, while their interactions with other international students who are also L2 users abroad have received far less attention, despite the ever-growing international student populations at European universities. This study examined students’ views regarding the role that lingua franca (LF) interactions with other international students played in their L2 acquisition, their L2 motivational development and their intercultural learning during study abroad. The data were derived from an empirical study that involved 81 German ERASMUS students who were studying in the UK for up to one academic year. The students’ views were elicited at the end of their stay with open-ended questionnaire items, and their verbal responses were analyzed using thematic content analysis. The analysis of the students’ reflections revealed a number of functions in each of the three areas, highlighting the potential of international student interactions as a viable source of L2 acquisition, L2 self-motivation, and intercultural learning during study abroad.